Antihypertensive drug utilization at health centres in a district of Istanbul - AKICI, AHMET; UĞURLU, MUSTAFA ÜMİT (SPRINGER, 2007)
Objective: Since irrational use of antihypertensives has considerable clinical and economical consequences, this study was conducted to evaluate antihypertensive drug utilization in hypertension at seven State Health Centres in Istanbul. Method: A total of 297 hypertensive patients who accepted to participate in the study were evaluated by a face-to-face questionnaire and a copy of their prescriptions were collected for prescription analysis. Results: Angiotensin-converting enzyme (ACE) inhibitors (31.7%), calcium channel blockers (28.8%), diuretics (16.2%), beta blockers (7.5%) and others (15.8%) have been prescribed. There were no statistically significant relation between prescribed antihypertensive drug groups and gender, age, and NSAIDs co-prescribing. The most frequent comorbidity in hypertensive patients was diabetes mellitus (10.4%) and calcium channel blockers (35.5%) have been prescribed to them as a first antihypertensive medication. Average cost per prescription was $42.7 +/- 38.1. According to the patients' self-reporting, the majority of them (85%) were prescribed without a physical examination. The physicians failed to write the prescriptions appropriately; only 5% of the scripts contained all information about the drug(s) and use instructions in full format. Conclusion: The present study indicates that GPs working at primary healthcare centres were rational in terms of antihypertensive drug choice. However, they poorly applied rational pharmacotherapy principles such as (a) writing a good prescription which is easily readable by the pharmacist and the patient and that contains full essential information; (b) a medical examination of the patient to assess her/his current clinical condition; and (c) taking care of not prescribing drugs with potential interaction like antihypertensives and NSAIDs together.
Keywords: hypertension; prescription; rational pharmacotherapy; general practitioner; Turkey; antihypertensives; GENERAL-PRACTITIONERS; RATIONAL PHARMACOTHERAPY; BLOOD-PRESSURE; HYPERTENSION; IMPACT; MANAGEMENT; PHYSICIANS; BLOCKERS